The case for an integrated approach to transition programmes at South Africa’s higher education institutions (Journal of Student Affairs in Africa, 2021)
This paper advocates an integrated approach to transition programmes at South Africa’s higher education institutions through drawing on the US literature on the first-year student experience and specific reference to behavioural interaction theory. The case for developing intentional and vertically integrated transition programmes is tied to: the need to understand the desired behaviours and learning outcomes at each stage of a student’s experience; an appreciation of the cognitive, psychosocial and identity development at different years of study; and a recognition of environmental influences and how they relate to, and can be adapted to, changing student characteristics and needs. Particular reference is made to Chickering and Reisser’s seven vectors of identity development, Baxter Magolda’s work on young adults’ journey toward self-authorship, and Bronfenbrenner’s developmental ecology model. It is concluded that an intentional, vertical integration of transition programmes requires horizontal alignment between objectives (desired behaviour), the developmental needs of students, and educational environments. In this regard, a number of recommendations for higher education instructional and support staff are proposed.
Keywords: Higher education; transition programmes; first-year student experience; behavioural interaction theory; United States; South Africa